The potential of Amomum tsao-ko as a traditional Chinese medicine: Traditional clinical applications, phytochemistry and pharmacological properties - Gang He; Shao-bing Yang; Yuan-zhong Wang (Arabian Journal of Chemistry, 2023)
In Southeast Asia, Amomum tsao-ko(A. tsao-ko) is a well-known plant spice that has both medicinal and edible value. A.tsao-ko was mainly used in the past for flavoring and aroma enhancement in cooking. It is also a medicinal plant used in folklore to treat diseases and is widely used in the therapeutic system. In China, A. tsao-ko is often used as a treatment or adjunct to the treatment of malaria, gastrointestinal disorders, epilepsy and cholera. This review describes in detail the traditional and folkloric uses, botanical studies, phytochemical components, and pharmacological activities of A. tsao-ko, elucidates its medicinal value as a traditional herbal medicine, and analyzes its potential for clinical applications. To provide reference for the comprehensive development and exploitation of A. tsao-ko in the fields of functional food, medicine and cosmetics. The available information about A. tsao-ko was collected through Web of Science, Google Scholar, PubMed, Baidu Scholar, Science Direct, China Knowledge Infrastructure (CNKI), and Springer Search. The keywords used included A. tsao-ko, essential oil, secondary metabolites, chemical composition, biological activity, pharmacology, traditional medicinal use, safety, and other related words. The literature of A. tsao-ko traditional and folk uses was retrieved from CNKI and Duxiu Search (https://www.duxiu.com/). The botany research information of A. tsao-ko was obtained through the Plant Plus of China website (https://www.iplant.cn). The economic value of A.tsao-ko can be obtained from Chinese herbal medicine industry information portal (https://www.zyctd.com/). So far, more than 493 chemical components have been isolated from A. tsao-ko. It possesses a variety of functions to maintain human health and protect the body from external influence, including regulating gastrointestinal function, antibacterial, anti-inflammatory, anti-tumor, regulating metabolic syndrome, and neuroprotection. In addition, A. tsao-ko is also an important cash crop in some areas, including southwest China, Vietnam, and northern Laos. Future research should focus on exploring the mechanisms between the single chemical constituents in A. tsao-ko and their pharmacological activities, as well as the relationship between their biological activities and medicinal clinical research.